2023
DOI: 10.1039/d3sm00744h
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity phase separation and defect lattices in the isotropic phase of active liquid crystals

Fernando Caballero,
Zhihong You,
M. Cristina Marchetti

Abstract: We use numerical simulations and linear stability analysis to study the dynamics of an active liquid crystal film on a substrate in the regime where the passive system would be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Besides active turbulence, stable vortex lattices with different symmetries have been reported in earlier experiments with swimming sperm cells [32] and an active microtubule-myosin motor mixture [33] and attributed to chiral motion of the active agents. Subsequently, many simulation studies of continuum models for active nematics [34][35][36] as well as of agent-based simulations [28,29] and continuum models for active polar fluids [37] exhibited vortex patterns of different symmetries. While most of continuum model studies assume constant density, recent work also has shown that vortex lattices precede turbulent clustering also in a model for compressible active fluids that allows for density fluctuations [38].…”
Section: Introductionmentioning
confidence: 99%
“…Besides active turbulence, stable vortex lattices with different symmetries have been reported in earlier experiments with swimming sperm cells [32] and an active microtubule-myosin motor mixture [33] and attributed to chiral motion of the active agents. Subsequently, many simulation studies of continuum models for active nematics [34][35][36] as well as of agent-based simulations [28,29] and continuum models for active polar fluids [37] exhibited vortex patterns of different symmetries. While most of continuum model studies assume constant density, recent work also has shown that vortex lattices precede turbulent clustering also in a model for compressible active fluids that allows for density fluctuations [38].…”
Section: Introductionmentioning
confidence: 99%